Two new secondary metabolites with antibacterial activities from Conyza aegyptiaca (Asteraceae) - Paul Etoga Mbarga; Hugues Fouotsa; Brigite Ndemangou; Julio Issah Mawouma Pagna; Ines Michèle Kanko Mbekou; Pierre Mkounga; Hans-Georg Stammler; Marcel Frese; Fabrice Boyom Fekam; Bruno Ndjakou Lenta; Norbert Sewald; Ephrem Augustin Nkengfack (Natural Product Research, 2023)

Antioxidant and cytotoxicity activities of δ-tocotrienol from the seeds of Allophylus africanus - Jean Francois Zeutsop; Joviale Nouboudem Zébazé; Raymond Ngansop Nono; Marcel Frese; Jean Rodolphe Chouna; Bruno Ndjakou Lenta; Pépin Nkeng-Efouet-Alango; Norbert Sewald (Natural Product Research, 2022)

Bioguided chemical study of Boswellia dalzielii Hutch. (Burseraceae) for antibacterial agents and a new glucopyranoxylmethoxybenzyle - Catherine Tegasne; Gilbert Deccaux Wabo Fotso Kapche; Isabelle Kamga Mawabo; Rostan Mangoua Talla; Jean-Bosco Jouda; Gervais Mouthé Happi; Bruno Ndjakou Lenta; Marcel Frese; Berhanu Molah Abegaz; Norbert Sewald (Natural Product Research, 2021)

Meleagrin from marine fungus Emericella dentata Nq45: crystal structure and diverse biological activity studies - Abdelaaty Hamed; Ahmed S. Abdel-Razek; Mariam Araby; Mohammed Abu-Elghait; Doaa G. El-Hosari; Marcel Frese; Hesham S. M. Soliman; Hans Georg Stammler; Norbert Sewald; Mohamed Shaaban (Natural Product Research, 2021)

Draft genome sequence of Streptomyces tunisialbus DSM 105760T - Ameni Ayed; Daniel Wibberg; Imène Zendah el Euch; Marcel Frese; Ferid Limam; Norbert Sewald (Archives of Microbiology, 2020)
Streptomyces strains are well known as promising source of bioactive secondary metabolites, important in ecology, biotechnology and medicine. In this study, we present the draft genome of the new type strain Streptomyces tunisialbus DSM 105760 T (= JCM 32165 T ), a rhizospheric bacterium with antimicrobial activity. The genome is 6,880,753 bp in size (average GC content, 71.85%) and encodes 5802 protein-coding genes. Preliminary analysis with antiSMASH 5.1.2. reveals 34 predicted gene clusters for the synthesis of potential secondary metabolites, which was compared with those of Streptomyces varsoviensis NRRL ISP-5346.

Isoshamixanthone: a new pyrano xanthone from endophytic Aspergillus sp. ASCLA and absolute configuration of epiisoshamixanthone - Reem A. Kamel; Ahmed S. Abdel-Razek; Abdelaaty Hamed; Reham R. Ibrahim; Hans Georg Stammler; Marcel Frese; Norbert Sewald; Mohamed Shaaban (Natural Product Research, 2020)

Terretonin O: a new meroterpenoid from Aspergillus terreus - Abdelaaty Hamed; Ahmed S. Abdel-Razek; Doha A. Omran; Mohammad M. El-Metwally; Doaa G. El-Hosari; Marcel Frese; Hesham S. M. Soliman; Norbert Sewald; Mohamed Shaaban (Natural Product Research, 2020)

Crystal structure and configuration revision of 9-hydroxy-7,8-dehydro-sarcotrocheliol and sarcotrocheliol - Abdelaaty Hamed; Marwa Y. Issa; Mohamed A. Ghani; Marcel Frese; Beate Neumann; Hans Georg Stammler; Norbert Sewald; Mohamed Shaaban (Natural Product Research, 2019)

X-ray, structural assignment and molecular docking study of dihydrogeodin from Aspergillus Terreus TM8 - Abdelaaty Hamed; Mohamed Ismail; Mohammad M. El-Metwally; Marcel Frese; Hans Georg Stammler; Norbert Sewald; Mohamed Shaaban (Natural Product Research, 2019)

3,4-Dihydro-quinolin-2-one derivatives from extremophilic Streptomyces sp. LGE21 - Manar M. Mahmoud; Ahmed S. Abdel-Razek; Marcel Frese; Hesham S. M. Soliman; Norbert Sewald; Mohamed Shaaban (Medicinal Chemistry Research, 2018)

Bioactive secondary metabolites from new terrestrial Streptomyces sp. TN82 strain: Isolation, structure elucidation and biological activity - Imene Zendah El Euch; Marcel Frese; Norbert Sewald; Slim Smaoui; Mohamed Shaaban; Lotfi Mellouli (Medicinal Chemistry Research, 2018)

Synthesis of diverse amide linked bis-indoles and indole derivatives bearing coumarin-based moiety: cytotoxicity and molecular docking investigations - Ahmed H. Halawa; Shimaa M. Abd El-Gilil; Ahmed H. Bedair; Essam M. Eliwa; Marcel Frese; Norbert Sewald; Mohamed Shaaban; Ahmed M. El-Agrody (Medicinal Chemistry Research, 2018)

Constitutive Expression of Interferon-Induced Human MxA Protein in Transgenic Tobacco Plants Does not Confer Resistance to a Variety of RNA Viruses - Michael Frese; Marcel Prins; Annette Ponten; Rob W. Goldbach; Otto Haller; Patric Zeltz (Transgenic Research, 2000)